2016
DOI: 10.1177/1849454416663660
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles shed from fibroblasts act as metalloproteinase carriers in a 3-D collagen matrix

Abstract: This study shows that fibroblasts migrating into a collagen matrix release numerous microvesicles into the surrounding medium. By spreading in regions of the matrix far distant from cells of origin, microvesicles carry metalloproteinase 9 (MMP-9) to act upon the collagen fibrils. As a result, the collagen matrix is gradually transformed from a laminar to a fibrillar type of architecture. As shown by western blots and gelatin zymography, MMP-9 is secreted as a 92 kDa precursor and activated upon release of 82 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Angiogenesis is promoted at low levels of endothelial-derived microvesicles containing active MMP-2 and MMP-9, while high levels of these MVs inhibit plaque angiogenesis which reduces the risk of rupture [35]. In addition, Lozito et al demonstrated that EVs secreted from endothelial cells are involved in the activation of MMP-2 initiating remodeling of the vascular matrix [36,37]. MMP-2 present in EC-derived vesicles also participates in neovascularization, promoting capillary structure formation and plaque rupture [25,38].…”
Section: Extracellular Vesicles As Mmps Carriersmentioning
confidence: 99%
“…Angiogenesis is promoted at low levels of endothelial-derived microvesicles containing active MMP-2 and MMP-9, while high levels of these MVs inhibit plaque angiogenesis which reduces the risk of rupture [35]. In addition, Lozito et al demonstrated that EVs secreted from endothelial cells are involved in the activation of MMP-2 initiating remodeling of the vascular matrix [36,37]. MMP-2 present in EC-derived vesicles also participates in neovascularization, promoting capillary structure formation and plaque rupture [25,38].…”
Section: Extracellular Vesicles As Mmps Carriersmentioning
confidence: 99%
“…In addition to the Rab GTPases, the kinesins could also drive cell surface exposure of MT1-MMP and promote CD44 shedding in primary macrophages [ 51 ]. Masci and colleagues propose that EVs dispersed along the fibroblast cell periphery contain abundance of MMPs [ 52 ]. The authors also demonstrate that the fusion of intraluminal vesicles with the outer membrane microvesicles (MVs) could act as a controlling mechanism during which MMP-9 is first activated (i.e., cleaved) and then released extracellularly.…”
Section: Mmps Secretion Into Evsmentioning
confidence: 99%
“…The regulation of EV-associated proteolytic activities plays active roles in physiological processes such as reproduction [ 52 ]. The gelatinases such as MMP-2 and MMP-9 found in the seminal vesicles and ventral prostate of Meriones libycus are involved in the seasonal reproductive cycle.…”
Section: Ev-associated Mmps: Roles In Immunosuppression and Reprodmentioning
confidence: 99%
See 1 more Smart Citation
“…The best structural conditions were provided by native collagen cryostructurates obtained by freeze‐drying of 1% w/v collagen gel in acetic acid, characterized by high matrix porosity and thick fiber bundles . Under these conditions, cells proliferated, migrated, and adhered to the collagen fibers through extended filopodia …”
Section: Introductionmentioning
confidence: 99%